Performances Evaluation And Comparison Of Two Algorithms For Fuzzy Logic Rice Cooking System (MATLAB Fuzzy Logic Toolbox And Fuzzy Tech) - Mohd Aras, Mohd Shahrieel; Abdul Azis, Fadilah; Ali, Fara Ashikin; Syed Abdul Hamid , Syed Mohamad Shazali; Md Basar, Mohd Farriz (2011)
This paper presents an evaluation of performances rice cooking system with using Intelligent Controller that is Fuzzy Logic Controller (FLC) to meet the special requirements and some limitations of the rice cooking system. A new inference scheme is given to estimate the amount of rice and water to be used, and the temperature will be controlled according to the amount of rice and the time while cooking. The FLC system is designed by using two types of simulation software which are MATLAB Fuzzy Logic Toolbox and FuzzyTECH. The results obtained from the both simulation software are given in this paper. The differences the between both simulation also will be discussed. MATLAB Toolbox gives more specific results compared FuzzyTECH software. The both software meet the special requirements because is not much differ between each other.